2010
DOI: 10.1007/s00300-010-0929-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal microbial processes in a high-latitude fjord (Kongsfjorden, Svalbard): I. Heterotrophic bacteria, picoplankton and nanoflagellates

Abstract: Temporal dynamics of the microbial food web in the Barents Sea and adjacent water masses in the European Arctic are to a large extent unknown. Seasonal variation in stocks and production rates of heterotrophic bacteria and phototrophic and heterotrophic picoplankton and nano-Xagellates was investigated in the upper 50 m of the highlatitude Kongsfjorden, Svalbard, during six Weld campaigns between March and December 2006. Heterotrophic bacteria, picoplankton and nanoXagellates contributed to ecosystem structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(63 citation statements)
references
References 85 publications
10
47
1
Order By: Relevance
“…The physical and biological characteristics of Kongsfjorden have been summarized by Hop et al (2006). Nitrogen limitation of primary production occurs during summer months (Rokkan Iversen and Seuthe, 2011), when stratification of the water column and input of nutrient-depleted glacial meltwater results in oligotrophic surface water in the inner fjord (e.g., increase proportion of cyanobacteria and cryptophytes in surface phytoplankton communities; Hop et al, 2002). Moreover, where turbid meltwater has yet to mix with clear sea water, phytoplankton growth is limited by reduced illumination (Svendsen et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…The physical and biological characteristics of Kongsfjorden have been summarized by Hop et al (2006). Nitrogen limitation of primary production occurs during summer months (Rokkan Iversen and Seuthe, 2011), when stratification of the water column and input of nutrient-depleted glacial meltwater results in oligotrophic surface water in the inner fjord (e.g., increase proportion of cyanobacteria and cryptophytes in surface phytoplankton communities; Hop et al, 2002). Moreover, where turbid meltwater has yet to mix with clear sea water, phytoplankton growth is limited by reduced illumination (Svendsen et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Only a few primary production measurements have been published from Kongsfjorden (Eilertsen et al 1989;Hop et al 2006;Piwosz et al 2009;Rokkan Iversen and Seuthe 2010) and only one from spring (Rokkan Iversen and Seuthe 2010). Our primary production measurements contribute with a considerable increase in time resolution for this important period of the year.…”
Section: Primary Productionmentioning
confidence: 99%
“…Either it will be grazed and recycled in the upper water masses or it may sink to deeper waters (Wassmann 1998). Recent research has also emphasized the importance of nanoplankton and picoplankton (Lovejoy et al 2007;Sakshaug et al 2009;Rokkan Iversen and Seuthe 2010) and showed that the concept of short, low-diversity polar food chains is overly simplistic (Smetacek and Nicol 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water masses in the Svalbard fjords are in the winter months well mixed with water temperatures ranging between −1.2 and 1.5 °C (Iversen and Seuthe 2011;Pawłowska et al 2011). Signals of a warming Arctic as reflected in raised surface air temperatures, a retreat and thinning sea ice cover, a longer melt season and increasing river discharges are observed since the 1980s (Serreze and Francis 2006;IPCC 2007;Bintanja and van der Linden 2013).…”
Section: Introductionmentioning
confidence: 99%